Public Transit and Micro-mobility: Identifying the Impacts of Bikeshare on Public Transit Ridership in the City of Chicago - (:unkn) unknown (My University, 2020)
ABSTRACT PUBLIC TRANSIT AND MICRO-MOBILITY: IDENTIFYING THE IMPACTS OF BIKESHARE ON PUBLIC TRANSIT RIDERSHIP IN THE CITY OF CHICAGO The variation of transit and bike share access amongst the communities in Chicago, in terms of their social, ethnic and economic segregation was investigated. The findings identify the area suitable for implementation of micro mobility as a first and last mile option. Based on transit connectivity and population mix, the communities are ranked into five groups: 1) Central: excellent transit and bike share access serving the micro mobility purpose; 2) North Side : good transit access which can be improved further amongst young age groups to improve transit ridership; 3) Far North Side : disproportionate transit and bike share distribution with excellent connectivity of transit and bike share in east and poor moving west; 4) North West , West and Near west and South west Side : has majority of hispanic population, black and low income population with a poor access to transit and bike share; 5) South Side, Far South West Side and Far South East side: high population of low income, senior , disability and black with very poor access to bus and bike share; Extensive improvement in transit service , bike share access and cost subsidy is needed. Severe imbalance exists in access to transit and bike share amongst the 77 communities in the city of Chicago. Bike share’s contribution towards increase or decrease in transit ridership was also investigated. A 25.9% increase in average bus stop level ridership and a 10.7% increase in average rail station level ridership was found to be associated with introducing bike share.
Keywords: Bike share; Equity; Micro-mobility; Transit